Experiences of peer workers and mental health service users with a peer support intervention: applying and critiquing a behaviour change techniques taxonomy. (4th May 2022) - Marks, J.; Sriskandarajah, N.; Aurelio, M. M.; Gillard, S.; Rinaldi, M.; Foster, R.; Ussher, M.
ABSTRACT: Objective: There is growing evidence for the benefits of peer support in mental health services. Less is known about the specific mechanisms whereby peer support brings about change. The aim of this study was to explore the experiences of adults using mental health services and peer workers to investigate whether the contents of an intentionally provided one-to-one peer support intervention can be adequately described using a standard taxonomy of behaviour change techniques (BCTs). Method: This qualitative comparative case study involved semi-structured interviews with 11 peer workers and 10 people they supported, in 2017–2018. They participated in a randomised controlled trial of a peer support intervention. Data were coded using both an analytical framework, derived from Michie and colleague's taxonomy of BCTs, and inductive thematic analysis. Results: The findings revealed that the intervention included BCTs from all 16 BCT groupings in the taxonomy, with the emphasis on the groupings of 'social support', 'comparison of behaviour', 'comparison of outcomes', 'regulation' 'shaping knowledge', 'identity' and 'covert learning'. Thematic analysis revealed a new group, 'relational aspects', consisting of five new BCTs: sharing of the peer worker's experiential knowledge; promoting reciprocity, autonomy, and confidentiality; and validation of a safe and trusting relationship. Discussion: A standard taxonomy of BCTs was shown to be broadly applicable to describing the contents of an intentional one-to-one peer support intervention for adults using mental health services. The taxonomy may need to be extended to consider additional BCTs related to encouraging the therapeutic relationship.